The skull evolution of oviraptorosaurian dinosaurs: the role of niche partitioning in diversification. (7th November 2019) - Ma, Waisum; Brusatte, Stephen L.; Lü, Junchang; Sakamoto, Manabu
Abstract: Oviraptorosaurs are bird‐like theropod dinosaurs that thrived in the final pre‐extinction ecosystems during the latest Cretaceous, and the beaked, toothless skulls of derived species are regarded as some of the most peculiar among dinosaurs. Their aberrant morphologies are hypothesized to have been caused by rapid evolution triggered by an ecological/biological driver, but little is known about how their skull shapes and functional abilities diversified. Here, we use quantitative techniques to study oviraptorosaur skull form and mandibular function. We demonstrate that the snout is particularly variable, that mandibular form and upper/lower beak form are significantly correlated with phylogeny, and that there is a strong and significant correlation between mandibular function and mandible/lower beak shape, suggesting a form–function association. The form–function relationship and phylogenetic signals, along with a moderate allometric signal in lower beak form, indicate that similar mechanisms governed beak shape in oviraptorosaurs and extant birds. The two derived oviraptorosaur clades, oviraptorids and caenagnathids, are significantly separated in morphospace and functional space, indicating that they partitioned niches. Oviraptorids coexisting in the same ecosystem are also widely spread in morphological and functional space, suggesting that they finely partitioned feeding niches, whereas caenagnathids exhibit extreme disparity in beak size. The diversity of skull form and function was likely key to the diversification and evolutionary success of oviraptorosaurs in the latest Cretaceous. Abstract : The two derived oviraptorosaur clades, oviraptorids and caenagnathids, are significantly separated in functional space, indicating that they partitioned niches. Oviraptorids coexisting in the same ecosystem are also widely spread in the functional space. The diversity of skull form and function was likely key to the diversification and evolutionary success of oviraptorosaurs in the latest Cretaceous.